Long- and short-range interaction footprints in entanglement entropies of two-particle Wigner molecules in 2D quantum traps - Cuestas, María Eloisa; Garagiola, Mariano; Pont, Federico Manuel; Osenda, Omar; Serra, Pablo (2025)
Artículo finalmente publicado en: Cuestas, M. E., Garagiola, M., Pont, F., Osenda, O., Serra, P. (2017). Long- and short-range interaction footprints in entanglement entropies of two-particle Wigner molecules in 2D quantum traps. Physics Letters A, 381 (27), 2153-2160. https://doi.org/10.1016/j.physleta.2017.05.003